First record of the genus Schizacea keifer (Acari : Eriophyidae) from Egypt, with description of a new species - El-Halawany, Ashraf S.; Mesbah, Amira E. (2015)
A new species of eriophyid mites from Egypt is described and illustrated. It is Schizacea aegyptimperata sp. nov. which has been found on Imperata cylindrical (L.) (Poaceae) from Egypt. This species is new to science and the genus is new record for Egyptian mite fauna. It causes rust on inner surface of leaves of the host plant. A key to the species of Schizacea of the world is provided. Key words: Eriophyidae, Schizacea, Imperata cylindrical, Poaceae, new species, Egypt.
Includes references.
Summary in Arabic.
1
Keywords: Aceria; Eriophyidae; Imperata cylindrica